2019
DOI: 10.37358/rc.19.5.7172
|View full text |Cite
|
Sign up to set email alerts
|

Conceptual Replication of Canine Serum Oxytocin Increase Following a Positive Dog-human Interaction

Abstract: The neurohormone oxytocin is known to exert a special function in the regulation of social relationships throughout vertebrate taxa. Recently it has been discovered that not only within-species, but in certain cases, between-species social bonds are also mediated by the same hormone, e.g. in case of the dog�human relationship. However, despite the exponential growth of findings at the behavioural level, there are still a lot of controversies on the biochemical assessment of oxytocin in canine samples. Thus, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 13 publications
0
9
1
Order By: Relevance
“…In our study, there was no significant difference in pre-and post-session salivary oxytocin concentrations, suggesting that the emotional state of the dogs remained stable pre-and post-session. Our result differs from other studies that have reported oxytocin level increases in dogs after positive interactions with humans (see, e.g., in [30][31][32]42,43]). Our methodology may explain why we did not observe an increase in oxytocin post-session: we did not want to interfere with the dynamics between the patients with FM and the AAA teams, and thus did not give any instructions to the patients on how to interact with the dogs.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In our study, there was no significant difference in pre-and post-session salivary oxytocin concentrations, suggesting that the emotional state of the dogs remained stable pre-and post-session. Our result differs from other studies that have reported oxytocin level increases in dogs after positive interactions with humans (see, e.g., in [30][31][32]42,43]). Our methodology may explain why we did not observe an increase in oxytocin post-session: we did not want to interfere with the dynamics between the patients with FM and the AAA teams, and thus did not give any instructions to the patients on how to interact with the dogs.…”
Section: Discussioncontrasting
confidence: 99%
“…The mean cortisol concentration levels pre-session for the dogs in our study were comparable to concentration levels reported in the literature [29]; less is known about oxytocin in dogs. The available data show greater variation [30][31][32]. This may be due to the fact that individual dog's oxytocin levels have a wide range.…”
Section: Discussionmentioning
confidence: 99%
“…Dog OT levels, as measured in blood, were found to increase following an interaction with a person (owner or familiar) [15,23,25,30,32] and in all such studies, social interactions involved either talking, eye contact, and stroking or just stroking for between 5 and a maximum of 30 min. Indeed, in the one study that compared these eliciting stimuli, physical contact involving stroking was shown to best trigger a rise in oxytocin [25].…”
Section: Discussionmentioning
confidence: 99%
“…However, more recently a number of authors have criticized the oversimplified view of OT’s role in social relationships in general [29] and in the dog-human relationship in particular [17]. Indeed, findings from the dogs’ perspective are inconsistent, with dogs’ endogenous OT levels being shown to increase following social interactions with their owner in some studies [15,27,30] but not in others [26,31]. Furthermore, in some studies dogs’ OT levels increased also after being stroked by a familiar person rather than the owner [22,32] calling into question the link between oxytocin and bonding.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies provide supporting evidence that dogs, at least in particular situations, find human social interaction intrinsically rewarding, and the quality of human interaction can modify even the hormonal level of dogs (for a review see Kis et al., 2017 ). Positive human interaction has the potential to increase oxytocin—a neurohormone related to attachment behaviors—( Hritcu et al., 2019 ; Kis et al., 2017 ) while social isolation (e.g. in case of shelter dogs) increases cortisol—a neurohormone associated with stress level ( Gunter et al., 2019 ).…”
Section: Introductionmentioning
confidence: 99%